1985
DOI: 10.1111/j.1600-0765.1985.tb00408.x
|View full text |Cite
|
Sign up to set email alerts
|

The pH of human crevicular fluid measured by a new microanalytical technique

Abstract: In physiological and pathological conditions, the pH of the crevicular fluid may play a significant role on the structure and function of the gingival crevice. In the present investigation the pH of human crevicular fluid was determined by a new microanalytical technique. The fluid was collected in 32 sites (19 patients) with capillary tubes. The tip of a double barreled, neutral carrier based microelectrode, highly selective for H+ ions was introduced directly into the capillary tubes containing either the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 17 publications
5
68
0
1
Order By: Relevance
“…3 This was also confirmed by Eggert et al who reported that 7% of subjects with periodontal disease had sites measuring pH 7.6 or higher. 4 Being asaccharolytic, gramnegative periodonto pathogenic bacteria, such as P. gingivalis, F. nucleatum and IjoIcr P. intermedia utilize proteins and amino acids as their energy source.…”
Section: 15supporting
confidence: 75%
“…3 This was also confirmed by Eggert et al who reported that 7% of subjects with periodontal disease had sites measuring pH 7.6 or higher. 4 Being asaccharolytic, gramnegative periodonto pathogenic bacteria, such as P. gingivalis, F. nucleatum and IjoIcr P. intermedia utilize proteins and amino acids as their energy source.…”
Section: 15supporting
confidence: 75%
“…Under physiological conditions O − # can be displaced from methaemoglobin by OH − , Cl − and H # O [23,24]. Thus the slightly alkaline pH found in i o in the inflamed gingival crevice and diseased periodontal pocket [25,26] would favour µ-oxo bishaem formation, since the displacement of superoxide from methaemoglobin by OH − would result in haemoglobin subunits containing Fe(III)PPIX.OH molecules. Proteolytically released Fe(III)PPIX.OH species would react together spontaneously, with the elimination of H # O, to form the…”
Section: Discussionmentioning
confidence: 99%
“…Gradients in the biofilm are not uniform and adjacent zones, with significantly different pHs, are detected. Bickel & Cimasoni (1985) showed that the pH in periodontal pockets may be as high as 9.0, but the interaction of reducing compounds with the metallic antimony pH electrodes used may have led to artefactual results (Eggert et al, 1991). Using glass micro-electrodes, Eggert and co-workers reported that 7 % of subjects with periodontal disease had sites measuring pH 7.6 or higher (Eggert et al, 1991), and concluded that there was no correlation between increased pH and periodontal pockets compared with healthy sites.…”
Section: Introductionmentioning
confidence: 99%